Regulation Of MicroRNA In Antiphospholipid Syndrome - Muhammad Shazwan Suhiman; Muhammad Aliff Mohamad; Asral Wirda Ahmad Asnaw; Nur Syahrina Rahim; Maiza Masri; Hayati Abdul Rahman; Nazefah Abdul Hamid; Nur Fariha Mohd Manzor (College of Pathologists, AMM, 2024)
Conference: The 2015 Annual Scientific Meeting of the College of Pathologists, Academy of Medicine Malaysia & 40th Anniversary Celebration of the Pathology AdvocatesAt: Berjaya Time Square Hotel, Kuala Lumpur